The Seed of Goal-Related Doubts: A Longitudinal Investigation of the Roles of Failure and Expectation of Success Among Police Trainee Applicants - Bettschart, Martin; Herrmann, Marcel; Wolf, Benjamin M.; Brandstätter, Veronika (Frontiers in Psychology, 2019)
Various theories on personal goal striving rely on the assumption that failure raises doubts about the goal. Yet, empirical evidence for an association between objective failure experiences and doubts about personal long-term goals is still missing. In a longitudinal field study, applicants for a job as a police trainee (n = 172, Mage = 25.15, 55 females and 117 males) were accompanied across three measurement times over a period of five months. We investigated the effects of failure and initial expectation of success (in the standardized selection process) on doubts regarding the superordinate goal of becoming a police officer. As hypothesized, both failure and low initial expectation of success as well as their interaction led to increased goal-related doubts over time. The findings provide first empirical evidence for the role of failure in the emergence of goal-related doubts in personal long-term goals and, therefore, the disengagement process as it is hypothesized in various theories on goal striving and life-span development.